# Welcome back

## Find a book, put up your feet, stay awhile

Sign in with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more

Download

Standard view

Full view

of .

Look up keyword

Like this

Share on social networks

9Activity

×

0 of .

Results for: No results containing your search query

P. 1

Algebra II/Pre-Calculus/Trigonometry Cheat SheetRatings: (0)|Views: 6,874|Likes: 8

Published by James Mishra

My original cheat sheet can be found at ( http://www.scribd.com/doc/56676187/Pre-Calculus-Semester-2-Cheat-Sheet ).

I decided to redesign it and add more information about trig identities and logarithms.

And since I felt like some people may prefer the old cheat sheet more, I made this as a new document rather than an update.

I decided to redesign it and add more information about trig identities and logarithms.

And since I felt like some people may prefer the old cheat sheet more, I made this as a new document rather than an update.

My original cheat sheet can be found at ( http://www.scribd.com/doc/56676187/Pre-Calculus-Semester-2-Cheat-Sheet ).

I decided to redesign it and add more information about trig identities and logarithms.

And since I felt like some people may prefer the old cheat sheet more, I made this as a new document rather than an update.

I decided to redesign it and add more information about trig identities and logarithms.

And since I felt like some people may prefer the old cheat sheet more, I made this as a new document rather than an update.

See more

See less

https://www.scribd.com/doc/64117938/Algebra-II-Pre-Calculus-Trigonometry-Cheat-Sheet

07/18/2013

text

original

P

RODUCT

TO

SUM

I

DENTITIES

sin

a

cos

b

=

sin

(

a

+

b

)+

sin

(

a

−

b

)

2

cos

a

sin

b

=

sin

(

a

+

b

)−

sin

(

a

−

b

)

2

cos

a

cos

b

=

cos

(

a

+

b

)+

cos

(

a

−

b

)

2

sin

a

sin

b

=

cos

(

a

−

b

)−

cos

(

a

+

b

)

2

S

UM

TO

PRODUCT

I

DENTITIES

sin

a

+

sin

b

=

2sin

(

a

+

b

2

)

cos

(

a

−

b

2

)

sin

a

−

sin

b

=

2cos

(

a

+

b

2

)

sin

(

a

−

b

2

)

cos

a

+

cos

b

=

2cos

(

a

+

b

2

)

sin

(

a

−

b

2

)

cos

a

−

cos

b

=−

2sin

(

a

+

b

2

)

sin

(

a

−

b

2

)

D

EGREES

AND

RADIANS

1

ο

=Π

180

radians

1

radian

=

180

Ο

Π

G

RAPHING

SINE

&

COSINE

y

=

a

sin

(

bx

+

c

)+

d

a

≠

0

b

≠

0

Amplitude =

∣

a

∣

Period =

2

Π

b

Frequency =

1

period

Phase shift =

−

c

∣

b

∣

Midline =

y

=

d

S

ECTORS

,

ARCS

,

AND

SPEED

Sector area =

r

Θ

2

Angular speed =

Θ

time

Linear speed =

r

Θ

time

Arc length=

r

Θ

L

AW

OF

SINES

(AAS, ASA)

sin

Aa

=

sin

Bb

=

sin

C c

L

AW

OF

COSINES

(SSS, SAS)

a

2

=

b

2

+

c

2

−

2bccos

A

A

MBIGUOUS

CASE

(SSA)

h

=

b

sin

A

a

=

opp

b

=

adj

I

F

A

IS

OBTUSE

a

≤

b

= No solution

a

>

b

= One solution

I

F

A

IS

ACUTE

a

<

ba

<

h

= No solution

a

<

b

a

=

h

= One solution

a

<

b

a

<

h

= Two solutions

a

≥

b

= One solution

A

REA

FOR

AAS, ASA

A

=

0.5a

2

sin

B

sin

C

sin

A

S

IGMA

NOTATION

∑

n

=

1

k

a

n

=

a

1

+

...

a

k

NTH

TERM

OF

ARITHMETIC

SEQUENCE

a

n

=

a

1

+(

n

−

1

)

d

d = common difference

S

UM

OF

ARITHMETIC

SERIES

S

n

=

n

2

(

a

1

+

a

n

)

S

n

=

n

2

[

2a

1

+(

n

−

1

)

d

]

NTH

TERM

OF

GEOMETRIC

SEQUENCE

a

n

=

a

1

r

n

−

1

r

=

a

2

a

1

;r

≠

1

r = commonratio

S

UM

OF

FINITE

GEOMETRIC

SERIES

S

n

=

a

1

(

1

−

r

n

1

−

r

)

S

n

=

a

1

−

a

n

r

1

−

r

S

UM

OF

INFINITE

GEOMETRIC

SERIES

S

=

a

1

1

−

r

∣

r

∣<

1

B

INOMIAL

EXPANSION

(

a

+

b

)

n

=

C

r n

a

n

−

r

b

r

where

r

= 0, 1, 2... n

B

INOMIAL

PROBABILITY

Prob

=

C

xn

p

x

q

n

−

x

n

independent trials,

p

probability of success,

q

= 1 –

p

P

ROPERTIES

OF

LOGARITHMS

Given that

b

>

0

;b

≠

1

:

log

b

x

=

a

→

b

a

=

x

log

b

b

=

1

log

b

1

=

0

log

b

b

x

=

x

b

log

b

x

=

x

Given that m and n are positive:

log

b

mn

=

log

b

m

+

log

b

n

log

b

mn

=

log

b

m

−

log

b

n

C

HANGE

OF

BASE

FORMULA

log

b

x

=

log

a

x

log

a

b

B

ASIC

TRIG

FUNCTIONS

sin

Θ=

opphyp

=

yr

cos

Θ=

adjhyp

=

xr

tan

Θ=

oppadj

=

y xcsc

Θ=

hypopp

=

r y

sec

Θ=

hypadj

=

r x

cot

=

adjopp

=

x y

P

YTHAGOREAN

IDENTITIES

sin

2

Θ+

cos

2

Θ=

1

tan

2

Θ+

1

=

sec

2

Θ

cot

2

Θ+

1

=

csc

2

Θ

C

OFUNCTION

IDENTITIES

sin

Θ=

cos

(

Π

2

−Θ

)

cos

Θ=

sin

(

Π

2

−Θ

)

tan

Θ=

cot

(

Π

2

−Θ

)

S

HIFT

I

DENTITIES

sin

(

Θ+Π

2

)

=+

cos

Θ

cos

(

Θ+Π

2

)

=−

sin

Θ

tan

(

Θ+

pi

2

)

=−

cot

Θ

O

DD

-E

VEN

I

DENTITIES

sin

(−Θ)=−

sin

Θ

cos

(−Θ)=

cos

Θ

tan

(−Θ)=−

tan

Θ

csc

(−Θ)=−

csc

Θ

sec

(−Θ)=

sec

Θ

cot

(−Θ)=−

cot

Θ

A

REA

FOR

SAS

A

=

0.5bcsin

A

P

OWER

R

EDUCING

I

DENTITIES

sin

2

Θ=

1

−

cos2

Θ

2

cos

2

Θ=

1

+

cos2

Θ

2

tan

2

Θ=

1

−

cos2

Θ

1

+

cos2

Θ

sin

2

Θ

cos

2

Θ=

1

−

cos4

Θ

8

S

UM

I

DENTITIES

sin

(

a

+

b

)=

sin

a

cos

b

+

cos

a

sin

b

cos

(

a

+

b

)=

cos

a

cos

b

−

sin

a

sin

b

tan

(

a

+

b

)=

tan

a

+

tan

b

1

−

tan

a

tan

b

D

IFFERENCE

I

DENTITIES

sin

(

a

−

b

)=

sin

a

cos

b

−

cos

a

sin

b

cos

(

a

−

b

)=

cos

a

cos

b

+

sin

a

sin

b

tan

(

a

−

b

)=

tan

a

−

tan

b

1

+

tan

a

tan

b

H

ALF

A

NGLE

I

DENTITIES

sin

Θ

2

=±

√

1

−

cos

Θ

2cos

Θ

2

=±

√

1

+

cos

Θ

2

tan

Θ

2

=±

√

1

−

cos

Θ

1

+

cos

Θ

tan

Θ

2

=

1

−

cos

Θ

sin

Θ

tan

Θ

2

=

sin

Θ

1

+

cos

Θ

D

OUBLE

A

NGLE

I

DENTITIES

sin2

Θ=

2sin

Θ

cos

Θ

tan 2

Θ=

2tan

Θ

1

−

tan

2

Θ

cos2

Θ=

cos

2

Θ−

sin

2

Θ

cos2

Θ=

2cos

2

Θ−

1

cos2

Θ=

1

−

sin

2

Θ

A

REA

FOR

SSS

A

=

√

s

(

s

−

a

)(

s

−

b

)(

s

−

c

)

s

=

a

+

b

+

c

2

Written by Rishabh Mishra. Licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported License. Version 20110912

You've already reviewed this. Edit your review.

1 hundred reads

1 thousand reads

tecthai liked this

Jignesh Patel liked this

Tracy Turner Cert HE liked this

Bobby Jones liked this

Alicia Patrick liked this

Nabeel liked this

et16 liked this

- Read and print without ads
- Download to keep your version
- Edit, email or read offline

© Copyright 2015 Scribd Inc.

Language

Choose the language in which you want to experience Scribd:

Sign in with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

Password Reset Email Sent

Join with Facebook

Sorry, we are unable to log you in via Facebook at this time. Please try again later.

or

By joining, you agree to our

read free for two weeks

Unlimited access to more than

one million books

one million books

Personalized recommendations

based on books you love

based on books you love

Syncing across all your devices

Join with Facebook

or Join with emailSorry, we are unable to log you in via Facebook at this time. Please try again later.

Already a member? Sign in.

By joining, you agree to our

to download

Unlimited access to more than

one million books

one million books

Personalized recommendations

based on books you love

based on books you love

Syncing across all your devices

Continue with Facebook

Sign inJoin with emailSorry, we are unable to log you in via Facebook at this time. Please try again later.

By joining, you agree to our

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

CANCEL

OK

You've been reading!

NO, THANKS

OK

scribd